Analisa Pengaruh Penerapan Enterprise Resource Planning (ERP) terhadap Kinerja Supply Chain Management (SCM) pada PT Toyota Astra Motor - Wirren Chang; Agnes Doraresta Khatarina Tokan; Delfina Muthia Sabella; Dewi Dewi; Mardiana Ng; Serina Serina; Wisnu Yuwono; Fitriana Aidnilla Sinambela (Institut Nalanda, 2023)
Technological developments in the world have changed companies to participate in using technology as a means of improving company performance. Companies can implement information technology systems that assist in terms of finance, company audits, and supply chain management (SCM) performance which is called enterprise resource planning (ERP). This study will discuss the effect of implementing ERP on SCM performance at the company PT Toyota Astra Motor. The method used is a qualitative approach and also a study of literature. PT Toyota Astra Motor has implemented an ERP application that is used, namely SAP (Standard Application Product in Data Processing) version ECC 6.0 and also has supply chain management which helps in expediting and accelerating the company's production and marketing processes to meet the needs of their consumers.